Pengembangan Media Pembelajaran Berbasis Video pada Mata Pelajaran Teknologi Informasi dan Komunikasi Sekolah Menengah Pertama: Development of Video-Based Learning Media in Information and Communication Technology Subjects in Middle Schools - Hendra Nelva Saputra; Zila Razilu; Sahrul Sahrul (ITScience (Information Technology and Science), 2025)
This study aims to develop video-based learning media using the Animaker application in the Information and Communication Technology (ICT) subject of Computer Systems for seventh-grade students in Junior High Schools, and to test the feasibility, practicality, and effectiveness of the resulting media. This study uses the Research and Development (R&D) method with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of three media experts, three material experts, one ICT teacher, and 15 seventh-grade students of SMP Negeri Satu Atap 1 Towea. Data collection techniques included observation, interviews, questionnaires, and documentation. The data obtained were analyzed using quantitative descriptive techniques with a Likert scale. The results showed that the Animaker video-based learning media obtained a very valid category with a percentage of 82.4% based on the assessment of media experts and 89.8% based on the assessment of material experts. The trial on students showed a very positive response with an average score of 4.60 or equivalent to a percentage of 92%, which indicates that the media is easy to use, interesting, and helps students understand the abstract material of Computer Systems. Furthermore, teachers found this media practical to use because it doesn't rely on a computer lab. Therefore, Animaker video-based learning media is deemed feasible, practical, and effective as an alternative ICT learning medium in schools, particularly in situations where technology-based learning facilities and infrastructure are limited.